Answer:
![\begin{gathered} x\text{ = -3} \\ y\text{ = 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5qh38rhbt61udei7ocbjnost9cfjwskvvt.png)
Step-by-step explanation:
Here, we want to solve the system of linear equations by elimination
We start by adding the two equations together since we can easily eliminate the y term
We have this as:
![\begin{gathered} (4x+x)\text{ +2y-2y = -8-7} \\ 5x\text{ + 0 = -15} \\ 5x\text{ = -15} \\ x\text{ = }(-15)/(5) \\ x\text{ = -3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y7lno8atjl2icari47vbtzoqo8fr8l10qq.png)
Finally, we want to get y
To get this, we have to eliminate x
We multiply the first equation by 1 and the second by 4, then subtract equation ii from equation i
We have this as:
![\begin{gathered} 1*\text{ (4x + 2y = -8} \\ 4*(x-2y\text{ = -7} \\ 4x\text{ + 2y=-8} \\ 4x\text{ - 8y -28} \\ 4x-4x+2y-(-8y)\text{ = -8-(-28)} \\ 2y\text{ + 8y = -8 + 28} \\ 10y\text{ = 20} \\ y\text{ = }(20)/(10) \\ y\text{ = 2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hcd9yx2zl6vhhm0t3gxc4yqnd2jnkxcr0m.png)